2019
DOI: 10.1016/j.ajog.2019.03.027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of parity on longitudinal maternal hemodynamics

Abstract: A. The aim of this study was to compare maternal hemodynamics between nulliparous and parous women with and without previous preeclampsia or small for gestational age. B. Parous women without history of preeclampsia or birth of small for gestational age neonates have the most ideal hemodynamic profile during pregnancy with greatest cardiac output and lowest peripheral vascular resistance; nulliparous women demonstrate a similar trend over gestation but with lower cardiac output and higher peripheral vascular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 68 publications
3
11
0
1
Order By: Relevance
“…The incidence of PE and small-for-gestational-age birth was highest in women with a previous history of PE who exhibited the poorest cardiovascular profile in pregnancy, leading the authors to conclude that there are parity-specific differences in maternal cardiac adaptation in pregnancy. 48 This pattern of hemodynamic response related to parity is consistent with the hypothesis that the maternal heart is conditioned in the first pregnancy, thereby eliciting improved maternal cardiovascular responses and improved placentation and lower PE rates in subsequent conceptions. 48…”
Section: Expert Reviewsupporting
confidence: 85%
See 2 more Smart Citations
“…The incidence of PE and small-for-gestational-age birth was highest in women with a previous history of PE who exhibited the poorest cardiovascular profile in pregnancy, leading the authors to conclude that there are parity-specific differences in maternal cardiac adaptation in pregnancy. 48 This pattern of hemodynamic response related to parity is consistent with the hypothesis that the maternal heart is conditioned in the first pregnancy, thereby eliciting improved maternal cardiovascular responses and improved placentation and lower PE rates in subsequent conceptions. 48…”
Section: Expert Reviewsupporting
confidence: 85%
“…48 This pattern of hemodynamic response related to parity is consistent with the hypothesis that the maternal heart is conditioned in the first pregnancy, thereby eliciting improved maternal cardiovascular responses and improved placentation and lower PE rates in subsequent conceptions. 48…”
Section: Expert Reviewsupporting
confidence: 85%
See 1 more Smart Citation
“…These women, in fact, show a more rapid rise in the cardiac output, an increase in the cardiac volume, and a fall in the peripheral vascular resistance during gestation, with all of these changes being of a greater magnitude when compared with the observations in nulliparous women. 36,54 Hemodynamic Measurements in Pregnancy Assessment of the cardiovascular function in pregnancy has become more relevant in the previous few decades because of the body of work reporting significant links between the maternal cardiovascular function and disorders such as preeclampsia, FGR, and gestational diabetes. Studies on cardiovascular function in association with preeclampsia have largely focused on the arterial function and circulatory hemodynamics.…”
Section: Scale On Left Axismentioning
confidence: 99%
“…As shown in a recent randomized trial of induction of labor at 39 weeks’ gestation versus expectant management, the effect of this temporal difference is to reduce the prevalence of preeclampsia by about 40%, thereby accounting for a significant proportion of the different rates of preeclampsia with parity [75]. Cardiac assessment of pregnancy has also consistently demonstrated that parous women have a more favorable cardiovascular profile throughout pregnancy compared to nulliparous women [76,77]. Such cardiac programming is a well-accepted phenomenon in non-pregnancy physiology, and provides a biologically plausible rationale for different rates of preeclampsia with parity.…”
Section: Apparent Inconsistencies With Cardiovascular Origin Hypotmentioning
confidence: 99%